Instructional Design of Local Wisdom-Based Flipbook Teaching Materials on Natural and Social Studies for Elementary School - Rahmawati, Septina; Abshor, Devy Aufia; Budianita, Avira; Nisa, Firda Khoirun; Maysaroh, Umi Kholifatul; Mahmudulhassan (Universitas Muhammadiyah Surakarta, 2025)
Elementary school curriculum changes by integrating science subjects into integrated science courses, requiring innovative open-ended materials based on local wisdom. This study aims to develop flipbook-based teaching materials integrating local wisdom for Natural and Social Studies (IPAS) learning at Darussalam Elementary School, focusing on enhancing students’ understanding and motivation, particularly in energy topics. Research and development (R&D) method with the Borg and Gall model, modified by Sugiyono. The first research flow is potential and problem, product design, design validation, design revision, final product, and field report preparation. The results demonstrated that the use of local wisdom-based flipbooks significantly improved student learning outcomes, as evidenced by increased understanding in pretest and posttest data. Expert assessments (lecturers, material experts, information technology experts, and school principals) confirmed that the teaching materials met the expected standards, with suggestions for enhancing interactivity. This research contributes to education by integrating technology and local wisdom to improve the quality of science learning in elementary schools. The findings indicate that flipbook-based technology can make learning more relevant and engaging for students. Future studies should focus on broader trials and long-term monitoring to evaluate the impact of these materials on student outcomes.